Meat-Free Mondays at Hospital Cafés in Aotearoa - Ella Ewens; Leanne Young; Sally Mackay (Medical Sciences Forum, 2023)
Reducing human meat intake contributes to a reduction in environmental degradation and non-communicable diseases, but meat-reduction policy interventions are limited, and globally, meat intake remains high. Meat-Free Mondays (MFM) is a global campaign to reduce meat consumption by 15% to improve human and planetary health. In 2020, Nelson Marlborough District Health Board (DHB) introduced an MFM policy at their staff and guest cafes, and Northland DHB trialled an MFM policy for two months. We conducted a mixed-methods investigation at these District Health Boards along with Auckland (who were not considering an MFM policy) of the attitudes of DHB staff and managers towards MFMs and the implementation barriers and enablers. We conducted an online staff survey at two DHBs and eleven semi-structured interviews with food-service managers, café managers, and sustainability managers. The online survey received 194 responses (105 from Auckland and 89 from Nelson and Marlborough). Of those surveyed, 51% were actively cutting back on meat, mainly for health and environmental concerns and enjoyment of plant-based dishes. Of those surveyed, 59% were positive towards MFMs, and 31% were negative. Qualitative analysis of the interviews and open-ended questions of the survey identified four key themes (1) ‘Change and choice’, MFMs’ impact on personal choice and resistance to changing eating habits; (2) ‘Getting it right—product and price’, food quality, appearance, nutritional balance, and the impact of an MFM policy on customer retention and sales; (3) ‘Human and planetary health’, the co-benefits of MFMs and hospitals as leaders in healthy, sustainable diets; (4) ‘Implementation success’, including consultation, communications, and education, for a successful MFM policy and maintaining staff wellbeing. Recommendations for the successful implementation of MFMs included wide consultation with food-service and DHB staff, the need to provide evidence on the success of MFMs and alternatives, consideration of the wider food environment, and provision of dietitian support for the food service.